2021
DOI: 10.3390/nu13030765
|View full text |Cite
|
Sign up to set email alerts
|

Free Sugars Intake among Chinese Adolescents and Its Association with Dental Caries: A Cross-Sectional Study

Abstract: This study aims to estimate the free sugars intake, identify the primary food sources of free sugars, and explore the relationship between free sugars intake and dental caries among Chinese adolescents. This cross-sectional study included 1517 middle-school students aged 12–14 years in Changsha city, China. Adolescents completed a 12-item Food Frequency Questionnaire (FFQ) and oral health assessment. The students’ dental caries experience was available as DMFT score (number of decayed, missing, and filled perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…To the best of our knowledge, this study is the first to characterize the current pattern of SSF consumption in medical college students according to sex and to explore the association between the MPAI and SSF intake in students from Shanghai, China. To date, most studies have addressed these issues in children or adolescents, but few have focused on college students [ 36 , 37 ]. Compared with children and adolescents, college students may consume higher SSF because of their characteristic independence and immaturity.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first to characterize the current pattern of SSF consumption in medical college students according to sex and to explore the association between the MPAI and SSF intake in students from Shanghai, China. To date, most studies have addressed these issues in children or adolescents, but few have focused on college students [ 36 , 37 ]. Compared with children and adolescents, college students may consume higher SSF because of their characteristic independence and immaturity.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies revealed the sugar and energy content of carbonated [18] and non-carbonated beverages [19] (including juice drinks, tea-based beverages, sports drinks and energy drinks) in Beijing, the sugar content of other common beverages, such as protein beverages, were still unclear, and the sample sizes were not big enough (93 carbonated beverages and 463 non-carbonated beverages). Besides, only 1 study took the quantity of sugar intake of children from beverages into account [20]. For this reason, it is our duty to focus on the sugar content in each beverage, the amount of sugar children took from the beverages each time, and whether the amount met the recommending standards or not under the current open policy.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of this study is particularly important when considering the increase in risk factors for LPR in China, such as the increasing of free sugars consumption and prevalence of obesity [ 10 , 38 , 39 , 40 , 41 ]. In our previous study, we found out that the daily consumption of free sugars was 53.1 g among adolescents, and 43.2% of the participants consumed more than 50 g/d of free sugars [ 42 ]. A meta-analysis summarized the trends in overweight and obesity among children and adolescents in China from 1991 to 2015 and found that the prevalence of overweight and obesity increased from 5.0% and 1.7% in 1991–1995 to 11.7% and 6.8% in 2011–2015, respectively [ 41 ].…”
Section: Discussionmentioning
confidence: 99%